OPPORTUNITIES AND CHALLENGES OF ISLAMIC BANKING IN INDONESIA IN FACING FREE MARKET COMPETITION - Mahmudah; Samsuddin (Dinar : Jurnal Prodi Ekonomi Syariah, 2025)
The development of Islamic banking in Indonesia is a manifestation of public demand for an alternative banking system which not only provides sound banking or financial services, but also adheres to sharia principles. This paper attempts to review the journey of Islamic banking in Indonesia which began with the issuance of Government Regulation No. 72 of 1992 concerning banks based on profit-sharing principles, which later officially became Islamic banks in 1998. This paper also seeks to offer solutions in facing the current challenges of Islamic banking development. As is already known, Islamic Banking in Indonesia has entered the age of twenty-two years, yet in terms of market share it is still relatively very small compared to national banking, namely less than 5%. This condition is considered very contradictory considering that the majority of Indonesia’s population is Muslim, although it does not rule out the possibility that non-Muslim communities may also participate in developing Islamic banking in Indonesia, because basically Islamic banks or Islamic banking are Islamic only in terms of their system which is based on Islamic sharia. The many opportunities and challenges faced by the Islamic banking industry require special strategies to develop Islamic banking in facing competition with conventional banking. These strategies are directed toward improving business competence comprehensively by referring to the analysis of the strengths and weaknesses of Islamic banking in Indonesia, such as the New Image Program, Market Segment Development Program, Product Development Program, Service Improvement Program, and Open and Universal Communication Program.